Self-phase modulation in various regimes of intense laser–plasma interactions. (17th December 2015) - Giulietti, Antonio; Giulietti, Danilo
Abstract : Creation of plasmas by intense laser pulses and consequent laser–plasma interactions involve highly non-linear processes. In particular, a variation of the refractive index induced by the laser action turns into a self-phase modulation (SPM) of the laser field. This effect, already observed with nanosecond laser pulses, achieves striking evidence with ultra-short pulses whose intensity can produce index changes in a time as short as a single optical cycle. In this condition, spectral modifications of the laser pulse produced by SPM may strongly modify the laser–plasma interaction. At the same time, the spectral analysis of the transmitted and scattered laser radiation gives valuable information on a variety of processes occurring in the plasma. In this paper we simply consider a few results, which can be attributed to SPM, with the aim of comparing nanosecond and sub-picosecond laser interaction regimes at moderate laser intensities.